Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve the following quadratic equation for complex solutions 3x^2- 7x + 11 = 0

Sagot :

To find the answer to this question, we have to use the quadratic formula:

[tex]x=\frac{-b^\pm\sqrt{b^2-4ac}}{2a}[/tex]

In this case, a has a value of 3, b has a value of -7 and c has a value of 11, replace for the given values:

[tex]\begin{gathered} x=\frac{-(-7)^\pm\sqrt{(-7)^2-4(3)(11)}}{2(3)} \\ x=\frac{7\pm\sqrt{49-132}}{6} \\ x=\frac{7\pm\sqrt{-83}}{6} \\ x=\frac{7\pm\sqrt{83}i}{6} \\ x1=\frac{7+\sqrt{83}i}{6} \\ x2=\frac{7-\sqrt{83}i}{6} \end{gathered}[/tex]

It means that the solutions of the equation are (7+√83i)/6 and (7-√83i)/6